‘Build knowledge’: the experience of a subject in health sciences - Pozzio, María (Universidad Nacional del Litoral, 2018)
This article describes the experience of the creation of Knowledge and Health Sciences, a subject belonging to the Common Cycle in Health -first year careers- of the Institute of Health Sciences of the Arturo Jauretche National University. The analysis is developed in the more general framework of the problematic relationship between social sciences and health, debated continuously for forty years in Latin America. Authors conclude that the notion of historicity and body have allowed them to achieve the pedagogical objectives, both at the content level and the competences.